1995
DOI: 10.1016/0014-5793(95)00849-5
|View full text |Cite
|
Sign up to set email alerts
|

Non‐enzymatic glycosylation of the dipeptide l‐carnosine, a potential anti‐protein‐cross‐linking agent

Abstract: The dipeptide carnosine (~-alanyl-L-histidine) was readily glycosylated non-enzymatically upon incubation with the sugars glucose, galactose, deoxyribose and the triose dihydroxyacetone. Carnosine inhibited glycation of actyl-Lys-His-amide by dihydroxyacetone and it protected c~-crystallin, superoxide dismutase and catalise against glycation and cross-linking mediated by ribose, deoxyribose, dihydroxyacetone, dihydroxyacetone phosphate and fructose. Unlike certain glycated amino acids, glycated carnosine was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
0
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(133 citation statements)
references
References 21 publications
3
123
0
5
Order By: Relevance
“…In our opinion, the hypothetical role(s) of carnosine-related dipeptides could be linked to some common feature(s) concerning the metabolism of these cell populations, although no direct evidence in this direction is at present available. Nevertheless, there is strong evidence that carnosine and structurally related dipeptides possess a wide range of properties, such as antioxidant, metal chelator, free radical scavenger, inhibitor of protein glycosilation (Boldyrev et al, , 1988(Boldyrev et al, , 1997Kohen et al, 1988;Boldyrev, 1993;Hipkiss et al, 1995;Preston et al, 1998; for review, see Hipkiss, 1998), which enable them to prevent several types of damage responsible for cell senescence (McFarland and Holliday, 1994;Sri-Kantha et al, 1996). Thus, carnosine-related dipeptides could exert a protective role in cell populations of the nervous system which, due to their location and/or function and metabolism, can come in contact with potentially harmful substances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our opinion, the hypothetical role(s) of carnosine-related dipeptides could be linked to some common feature(s) concerning the metabolism of these cell populations, although no direct evidence in this direction is at present available. Nevertheless, there is strong evidence that carnosine and structurally related dipeptides possess a wide range of properties, such as antioxidant, metal chelator, free radical scavenger, inhibitor of protein glycosilation (Boldyrev et al, , 1988(Boldyrev et al, , 1997Kohen et al, 1988;Boldyrev, 1993;Hipkiss et al, 1995;Preston et al, 1998; for review, see Hipkiss, 1998), which enable them to prevent several types of damage responsible for cell senescence (McFarland and Holliday, 1994;Sri-Kantha et al, 1996). Thus, carnosine-related dipeptides could exert a protective role in cell populations of the nervous system which, due to their location and/or function and metabolism, can come in contact with potentially harmful substances.…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine has been shown to act as a competitive inhibitor of non-enzymic glycosylation of proteins (Hipkiss et al, 1995). This consists of a series of posttranslational modifications in which protein amino groups and side chains react non-enzymatically with monosaccharides (forming the so called 'Amadori products'; Munch et al, 1997).…”
Section: Inhibition Of Protein Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the Amadori reaction that is involved in the non-enzymic glycosylation of proteins and the subsequent production, via the Maillard reaction, of advanced glycation end products (AGEs, reviewed by Monnier 1988). Carnosine reacts more strongly than lysine with various sugars and it has been suggested that its role in the cell is to act as a competitive inhibitor of non-enzymic glycosylation of proteins (Michaelis et al, 1992;Hipkiss et al, 1994Hipkiss et al, , 1995. Furthermore, it has been shown that carnosine reacts rapidly with the triose phosphate sugar intermediates of glycolysis, particularly glyceraldehyde phosphate and dihydroxyacetone phosphate (A Stevens, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the expansion of the imidazole ring content in human skeletal muscle through an increase in the muscle carnosine concentration o ers a means to increase muscle bu ering capacity and high intensity exercise performance and capacity [1][2] . Other potential physiological roles of carnosine, such as increased calcium sensitivity [3][4] and antioxidant capacity [5][6] might also contribute to a positive e ect on exercise capacity and performance, although literature is inconclusive 7 .…”
Section: Introductionmentioning
confidence: 99%